2019
DOI: 10.1186/s40729-019-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone formation following the osteotome sinus floor elevation technique without grafting using cone beam computed tomography: a preliminary study

Abstract: Background Osteotome sinus floor elevation (OSFE) is used to increase the bone volume at the site of the maxillary sinus through the transalveolar approach. However, there is uncertainty regarding the necessity of the use of grafting material in order to maintain the space for new bone formation. Objective This study aimed to evaluate new bone formation 6 months after osteotome sinus floor elevation without grafting and to evaluate the correlations between residual bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The inclusion criteria for this study were partially edentulous patients with a unilateral loss of teeth in the maxillary molar or premolar areas with severe atrophy and a residual alveolar ridge height of less than 5 mm. Both MPM and β-TCP showed clinically satisfactory results, but in the literature, there are many studies such as osteotome sinus floor elevation technique [52] and osseodensification [53] when residual bone height is limited in maxillary posterior region. Further investigations were needed for extreme atrophic cases (for example 0-1 mm residual height) whether MPM could be successful.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria for this study were partially edentulous patients with a unilateral loss of teeth in the maxillary molar or premolar areas with severe atrophy and a residual alveolar ridge height of less than 5 mm. Both MPM and β-TCP showed clinically satisfactory results, but in the literature, there are many studies such as osteotome sinus floor elevation technique [52] and osseodensification [53] when residual bone height is limited in maxillary posterior region. Further investigations were needed for extreme atrophic cases (for example 0-1 mm residual height) whether MPM could be successful.…”
Section: Discussionmentioning
confidence: 99%
“…The bone tended to increase in the first three years and then became stable afterwards. In 2019, Suk-Arj et al 11 conducted a study on osteotome sinus floor elevation without grafting material with short term 6 months follow-up period. They revealed that the average of ESBG was 1.80 ± 0.79 mm and 1.96 ± 0.67 mm in the coronal and sagittal view respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation was based on the radiographic outcome of endo-sinus bone gain. According to Suk-Arj et al, 11 the endo-sinus bone gain in the osteotome group was 1.96 ± 0.67 mm and the estimated minimum clinical important difference was 1.3 based on expert's opinion. By adopting a two-sided 5% significance level and a power of 80%, a predicted sample size of 5 patients per group was necessary.…”
Section: Methodsmentioning
confidence: 97%
“…The average IPL in some studies was around 2 mm and achieved a high percentage of ESBG [ 22 , 23 , 34 ]. Thus, we selected 2 mm as the first interval point in this study in order to see whether the %ESBG would be higher with a IPL over than 2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies [14,[20][21][22][23] have found that the IPL was positively correlated with the endo-sinus bone gain (ESBG) following non-grafting OSFE. The protruding implant was considered as the maintenance for endosinus space under the elevated membrane, which contributes to bone formation around implants [22]. Therefore, greater ESBG can be obtained with a longer IPL.…”
Section: Introductionmentioning
confidence: 99%